Verity or Deception? On the Information of Ahmād al-Balādurī about the Byzantine Empire in the 7th Century - Pentek, Zdzisław (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
The text concerns a short analysis of fragments of the Arab chronicle Kitāb futūh. al-buldān (Book of the Conquest of Countries) by Ah. mād ibn Yahyā ibn Jābir Al-Balādhurī (died in 892). The analysis involves the perception of the Byzantine Empire in the 7th century.